Application SF 36 And EQ 5D To Assess Quality Of Life In Musculo-Skeletal Health Of Elderly Patiens To Determine Intervention: Systematic Review - Dewi, Desak Wayan Suarse Dewi; HASSAN, HAFIZAH CHE HASSAN; NAMBIAR, NISHA NAMBIAR (Holistic Nursing Plus, 2024)
Background: Elderly Patients which  chronic Kidney Diseases on Haemodialysis (HD) experience impaired muscle strength related quality of life (QoL). We analysed HD  relationship with physical performance, body composition, and muscle strength; Purpose: To asses QoL in muscle-skeletal health and functional Capacity on elderly Chronic Kidney Diseases maintenance Haemodialysis. Methods: Using systematic literature review with data base EBSCO, ELSIVIER, Pup Med, Science Direct, Walley, start search year 2020-2023, 13 articles Randomize control trial and cross sectional. Groups underwent the following assessments physical QoL using application of the SF-36 questionnaire , and the Euro QoL five item psychologic-questionnaire (EQ-5D) are two of the most popular.  Observed 6-minute walk test (6MWT) and handgrip strength, one-repetition maximum of knee flexors and extensors. Result: Main approaches, namely generic and disease-specific instruments, can be applied to measure health-related quality of life, the short form 36 questionnaire (SF-36) and the Euro QoL five item questionnaire (EQ-5D) are two of the most popular. One of the main goals of any interventions to prevent and cure musculoskeletal problems in the ageing population with should be to improve quality of life. Conclusion: To measure health-related quality of life, two basic methods can be used: The EQ-5D and the short form 36 questionnaire. Overview surveys are used to measure the quality of life related to health in individuals suffering from musculoskeletal illnesses. The validation of therapeutic and preventive interventions in this field should be aided by the recent development of specific instruments.